TCR microclusters form spatially segregated domains and sequentially assemble in calcium-dependent kinetic steps - Jason Yi (Nature Portfolio, 2019)
Engagement of T cell receptors (TCRs) induces the formation of microclusters that mediate the downstream signalling events. Here the authors show, using high resolution TIRF-SIM and live cell imaging, that ZAP70 and LAT are recruited to TCR with distinct kinetics, with the delayed ZAP70-TCR association modulated by TCR-induced calcium flux.